Functional Neuroimaging of Avoidance Habits in Obsessive-Compulsive Disorder - Gillan, Claire M.; Apergis-Schoute, Annemieke M.; Morein-Zamir, Sharon; Urcelay, Gonzalo P.; Sule, Akeem; Fineberg, Naomi A.; Sahakian, Barbara J.; Robbins, Trevor W. (The American journal of psychiatry, 2015)
Objective:The purpose of this study was to determine the neural correlates of excessive habit formation in obsessive-compulsive disorder (OCD). The authors aimed to test for neurobiological convergence with the known pathophysiology of OCD and to infer, based on abnormalities in brain activation, whether these habits arise from dysfunction in the goal-directed or habit system.Method:Thirty-seven OCD patients and 33 healthy comparison subjects learned to avoid shocks while undergoing a functional MRI scan. Following four blocks of training, the authors tested whether the avoidance response had become a habit by removing the threat of shock and measuring continued avoidance. Task-related differences in brain activity in three regions of interest (the caudate, the putamen, and the medial orbitofrontal cortex) were tested at a statistical threshold set at <0.05 (family-wise-error corrected).Results:Excessive habit formation in OCD patients, which was associated with hyperactivation in the caudate, was observed. Activation in this region was also associated with subjective ratings of increased urge to perform habits. The OCD group, as a whole, showed hyperactivation in the medial orbitofrontal cortex during the acquisition of avoidance; however, this did not relate directly to habit formation.Conclusions:OCD patients exhibited excessive habits that were associated with hyperactivation in a key region implicated in the pathophysiology of OCD, the caudate nucleus. Previous studies indicate that this region is important for goal-directed behavior, suggesting that habit-forming biases in OCD may be a result of impairments in this system, rather than differences in the buildup of stimulus-response habits themselves.